Stability of oral and fecal microbiome at room temperature: impact on diversity - Rius-Sansalvador, Blanca; Bars-Cortina, David; Khannous-Lleiffe, Olfat; Garcia-Serrano, Ainhoa; Guinó, Elisabet; Saus, Ester; Gabaldón, Toni; Moreno, Victor; Obón-Santacana, Mireia (Frontiers in Microbiomes, 2025)
IntroductionWhen collecting oral and fecal samples for large epidemiological microbiome studies, optimal storage conditions such as immediate freezing are not always feasible. It is essential to study the impact of temporary room temperature (RT) storage on microbiome diversity.MethodsWe conducted a pilot study to validate a sampling protocol based on the viability of 16S rRNA gene sequencing in microbiome samples. Fecal and oral samples from five participants were collected and preserved under different conditions: a) 70% ethanol; b) FIT tube for stool; and c) chlorhexidine solution for oral wash. Four aliquots per sample were stored at RT and frozen at days 0, 5, 10, and 15.ResultsAlpha diversity showed a maximum average decrease of 0.3%, 1.6%, and 1.7% after 5 days for oral, stool in ethanol, and stool in FIT samples, respectively. The relative abundances of the main phyla and orders remained stable throughout the 15 days.DiscussionMicrobiome diversity appears remarkably resilient. Fecal and oral samples stored at RT in 70% ethanol, chlorhexidine, and FIT tubes exhibited minimal changes over 15 days. These results support the feasibility of large-scale microbiome studies with delayed sample processing.